A nanogold resonance Rayleigh scattering method for determination of trace As based on the hydride nanoreaction. (13th January 2015) - Jiang, Caina; Chen, Chunqiang; Lu, Zujun; Liu, Qingye; Tang, Meiling; Liang, Aihui; Jiang, Zhiliang
Abstract In H2SO4 solution, As(III) was reduced to arsine (AsH3) by NaBH4, and was absorbed in HAuCl4 solution to form nanogold particles (NGs) that exhibited a resonance Rayleigh scattering (RRS) effect at 370 nm. Under the selected conditions, when the As(III) concentration increased the RRS peak also increased due to the formation of more NGs. There was a linear correlation between RRS intensity and As(III) concentration in the range 6–1000 ng/mL, with a detection limit of 3 ng/mL. This new hydride generation–nanogold reaction RRS (HG–NG RRS) method was applied to determine trace amounts of As in milk samples, with satisfactory results. Copyright © 2015 John Wiley & Sons, Ltd.